Pelaksana Teknis Kegiatan Kejuaraan Provinsi (Kejurprov) Cabang Olahraga Atletik Tahun 2023 - Martiani Martiani; Roni Syaputra; Linda Herlina; Habib Novrian Putra (Jurnal Dehasen Untuk Negeri, 2024)
A variety of sports disciplines, including running, leaping, and throwing competitions, make up the sport of athletics. Numerous sports requiring running, walking, jumping, and throwing are included in the category of athletics. The focus of community service projects is the Bengkulu KEJURPROV (Kejuaraan Atletik Provinsi) activities for 2023. In capacity as an officer on the committee overseeing the 2023 Bengkulu KEJURPROV (Provincial Athletics Championship) events, represents the competition apparatus on a regional level. The event was organized by lecturers and students in the Physical Education Study Program at Faculty of Teacher Training and Education Dehasen University Bengkulu. The results obtained from this community service activity were 2 lecturers as referees and 25 students as timers, committee members and committee secretaries from the Physical Education Study Program, Faculty of Teacher Training and Education, Dehasen University, Bengkulu